Characterization of an RF translator for WiFi communication over TV white spaces - Ramirez, Patth Rick L.; Marciano, Joel Joseph S. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
This study describes a radio frequency (RF) front-end that enables direct RF translation of an IEEE 802.11 signal at 2.4GHz ISM band to UHF TV frequencies (470-800MHz). Specifically, the intention is to allow 2.4GHz IEEE 802.11 or WiFi-compliant radios to be used for opportunistic communication at so-called TV white spaces (TVWS). In order to investigate if WiFi signals can be faithfully translated to TVWS frequencies, parametric and functional tests were performed using the RF translator. The tests are conducted for different 2.4GHz WiFi channels at the input, and for different target TV channel frequencies at the output of the RF translator. We present the results of single-tone spurious response and spectral mask tests in order to characterize the nonlinear behaviour of the RF translator. The performance was found to vary significantly across the 2.4GHz input frequencies with WiFi channel 11 (2.462GHz) providing the best results. In addition, we evaluate the system functionality by measuring EVM (Error Vector Magnitude) and TCP (Transmission Control Protocol) throughput with and without the RF translator and compare the results with the spurious response tests. The results show that the signal distortion caused by the spurious emissions contributes to degrading the measured EVM, RSSI (Received Signal Strength Indicator) and throughput levels. In particular, the higher EVM and lower RSSI & peak throughput values achieved at certain output TV channel frequencies are consistent with the high levels of spurious response that were measured in those cases.
Thesis (M.S. Electrical Engineering)--University of the Philippines Diliman
Keywords: Radio frequency; IEEE 802.11 (Standard); Wireless communication systems